Insights into the use of mesenchymal stem cells in COVID-19 mediated acute respiratory failure - Durand, Nisha (NPJ Regen Med, 2020)
The emergence of severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) at the end of 2019 in Hubei province China, is now the cause of a global pandemic present in over 150 countries. COVID-19 is a respiratory illness with most subjects presenting with fever, cough and shortness of breath. In a subset of patients, COVID-19 progresses to hypoxic respiratory failure and acute respiratory distress syndrome (ARDS), both of which are mediated by widespread inflammation and a dysregulated immune response. Mesenchymal stem cells (MSCs), multipotent stromal cells that mediate immunomodulation and regeneration, could be of potential benefit to a subset of COVID-19 subjects with acute respiratory failure. In this review, we discuss key features of the current COVID-19 outbreak, and the rationale for MSC-based therapy in this setting, as well as the limitations associated with this therapeutic approach.